Stressful Life Events and Depression Symptoms: The Effect of Childhood Emotional Abuse on Stress Reactivity - Shapero, Benjamin G. (2013)
OBJECTIVE: Stressful life events are associated with an increase in depressive symptoms and the onset of major depression. Importantly, research has shown that the role of stress changes over the course of depression. The present study extends the current literature by examining the effects of early life stress on emotional reactivity to current stressors. METHOD: In a multiwave study (N = 281, mean age = 18.76; 68% female), we investigated the proximal changes that occur in depressive symptoms when individuals are faced with life stress and whether a history of childhood emotional abuse moderates this relationship. RESULTS: Results support the stress sensitivity hypothesis for early emotional abuse history. Individuals with greater childhood emotional abuse severity experienced greater increases in depressive symptoms when confronted with current dependent stressors, controlling for childhood physical and sexual abuse. CONCLUSIONS: This study highlights the importance of emotional abuse as an indicator for reactivity to stressful life events.